1992
DOI: 10.1007/bf02382761
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive parameters of female Japanese macaques: Thirty years data from the arashiyama troops, Japan

Abstract: ABSTRACT. Over a 30-year period from 1954 to 1983, 975 live births were recorded for Japanese macaque females at the Iwatayama Monkey Park, Arashiyama, Japan. Excluding unknown birth dates, primiparous mothers gave birth to 185 infants (182 cases with age of mother known) and multiparous mothers gave birth to 723 infants (603 cases with age of mother known). The peak month of birth was May with 52.3% of the total births occurring during the period. Multiparous females who had not given birth the previous year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
80
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 41 publications
(41 reference statements)
6
80
1
1
Order By: Relevance
“…Symbols indicate studies from the same sites as follows. ࡗ, Amboseli, Kenya (13,18); OE, Davis, CA (14,43); ᮀ, Madingley, U.K. (15,31,36); F, Salem, Germany (21, 39); E, Cayo Santiago, Puerto Rico (19,26,27); ‚, Ketambe, Indonesia (47,48); छ, Rome, Italy (25, 41); s, Arashiyama, Japan (32,46). For other definitions, see the legend for Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Symbols indicate studies from the same sites as follows. ࡗ, Amboseli, Kenya (13,18); OE, Davis, CA (14,43); ᮀ, Madingley, U.K. (15,31,36); F, Salem, Germany (21, 39); E, Cayo Santiago, Puerto Rico (19,26,27); ‚, Ketambe, Indonesia (47,48); छ, Rome, Italy (25, 41); s, Arashiyama, Japan (32,46). For other definitions, see the legend for Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Simpson and Simpson, 1982); and some suggest similar investments in both sexes (e.g. Koyama et al, 1992). Thus, previous studies are highly inconsistent (Brown, 2001).…”
Section: Introductionmentioning
confidence: 95%
“…Provisioned Japanese macaques (Macaca fuscata) are useful to examine sex-biased maternal investment using various parameters based on large sample size because inconsistent, but interesting, results have been reported-a male-biased birth sex ratio among high-ranking females (Aureli et al, 1990), longer interbirth intervals after rearing daughters than after sons (Takahata et al, 1995), and no sex-biased maternal investment (Koyama et al, 1992). There are abundant data on reproduction and infant growth in a provisioned, free-ranging Japanese macaque population at Takasakiyama, in the southern region of Japan (Kurita et al, 2002(Kurita et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Many detailed investigations have been conducted on the reproductive parameters, including birth rate and time, of provisioned Japanese monkey troops [4,[6][7][8][10][11][12]. Since the nutritional status of individual animals can be improved by artificial feeding, substantial changes have been observed in the reproductive parameters of provisioned troops [7,11].…”
mentioning
confidence: 99%
“…Koyama et al [6] compared delivery dates in the Arashiyama troop by age and pregnancy history. Subsequently, they found that 4-year-old primiparous monkeys had later delivery dates (mean delivery date in midJune) than monkeys aged 5 or more years (mean delivery date in late May).…”
mentioning
confidence: 99%